Metallothionein polymorphisms in a Northern Spanish population with neovascular and dry forms of age-related macular degeneration. (3rd September 2017) - García, Montserrat; Álvarez, Lydia; Fernández, Ángela; González-Iglesias, Héctor; Escribano, Julio; Fernández-Vega, Beatriz; Villota, Eva; Fernández-Vega Cueto, Luis; Fernández-Vega, Álvaro; Coca-Prados, Miguel
ABSTRACT: Background : To elucidate the potential role of single nucleotide polymorphisms (SNPs) in the metallothionein (MT) genes in Northern Spanish patients with age-related macular degeneration (AMD). Methods : A total of 130 unrelated Northern Spanish natives diagnosed with AMD (46 dry, 35 neovascular, and 49 mixed) and 96 healthy controls, matched by age and ethnicity, were enrolled in a case–control study. DNA was isolated from peripheral blood and genotyped for 14 SNPs located at 5 MT genes ( MT1A : rs11076161, rs 11640851, rs8052394, and rs7196890; MT1B : rs8052334, rs964372, and rs7191779; MT1M : rs2270836 and rs9936741; MT2A : rs28366003, rs1610216, rs10636, and rs1580833; MT3 : rs45570941) using TaqMan probes. The association study was performed using the HaploView 4.0 software. Results : The allelic and genotypic frequencies analysis revealed that rs28366003 at MT2A gene is significantly associated with dry AMD. The frequency of genotype AG was significantly higher in dry AMD than in control cases ( p = 2.65 × 10 −4 ; AG vs. AA) conferring more than ninefold increased risk to dry AMD (OR = 9.39, 95% CI: 2.11–41.72), whereas the genotype AA confers disease protection (OR = 0.82, 95% CI: 0.71–0.95). No statistically significant differences were observed between AMD subjects and controls in the rest of the 14 SNPs analyzed. Conclusions : The present study is the first to investigate the potential association of SNPs at MT genes with susceptibility to AMD. We found a significant association of SNP rs28366003 at MT2A gene with susceptibility to the dry form of AMD in a Northern Spanish population.